Analysis of CSN2 variants in Friesian Holstein cows and their association with milk protein allergy and production traits - Mohammad Ilham Dhiaurridho; Firmansyah Tristadika Prakosa; Firna Fauziatul Karimah; Salsabilla Ramadhana; Ine Febriantama; Thoriq Aldri Bramastya; Ahmad Pramono; Muhammad Cahyadi (Universitas Sebelas Maret, 2022)
Objective: The objective of this study was to analyze CSN2 variants in Indonesian Friesian Holstein (FH) cow and their association with milk protein allergy and production traits.Methods: Genomic DNA was extracted from bloods of twelve Indonesian FH cow. Exon 7 of the CSN2 was amplified using novel primer pair to produce 683 bp amplicon. The primers were 5’-ACCCCAATTTCTTAACCAAACCA-3’ as a forward primer and 5’-CATCAGAAGTTAAACAGCACAGT-3’ as a reverse primer. The PCR products were analyzed to determine the nucleotide sequence of CSN2 using Bioedit version 7.2.5. Moreover, Hardy-Weinberg equilibrium (HWE) was calculated and one-way analysis of variance (ANOVA) was conducted to associate between CSN2 variants and milk production traits.Results: Two polymorphisms, c.350A>C and c.516G>C, were identified in the CSN2 exon 7. Base substitution from adenine (A) to cytosine (C) of c.350A>C changed amino acid codon from histidine (CAU) to proline (CCU), and base substitution guanine (G) to cytosine (C) of c.516G>C changed amino acid codon from arginine (AGG) to serine (AGC). The CC genotype frequency for c.350A>C SNP was 33% and they were able to produce A2 CSN2 variant which is favorable for preventing lactose intolerance. In addition, there were no association between c.350 A>C and c.516 G>C SNP of the CSN2 with milk production traits.Conclusions: In conclusion, A1 and A2 variants of CSN2 were identified in Indonesian FH population and they did not associate with milk production in Indonesian FH.